Dynamics and control of a radial-flow ammonia synthesis reactor - Schbib, Noemi Susana (2001)
The steady- and non steady-state simulation of an industrial ammonia converter is presented. The reactor includes two adiabatic radial-flow catalyst beds in series. An interbed (gas-gas) heat exchanger is used to preheat the feed stream. The steady-state results showed good agreement with plant data. The influence of different disturbances (feed composition and temperature, reactor pressure) on the dynamic evolution of the main variables is analysed. The open-loop and closed-loop operation is compared from the standpoint of the reactor stability. © 2001 Elsevier Science Ltd. All rights reserved.